Comparison of host innate immune response of human and porcine airway epithelial cells and anti-influenza exploitation - Yang, Jiayun (2021)
Influenza A virus (IAV) infection is a major global disease that continues to threaten wildlife, livestock production and human health. In humans, IAV infection can be severe leading to the complication of host hyperacute inflammatory response, also known as ‘cytokine storm’, with ensuing high mortality rate. Pigs infected with IAVs, however, often display no or only mild symptoms. Viral RNA is principally recognised by pattern-recognition receptors retinoic inducible gene-1 (RIG-I) and Toll-like receptor 7/8 (TLR 7/8), each of which signals to activate two key transcription factors, nuclear factor kappa B (NF-ĸB) and interferon regulatory factor 3 (IRF3), for the induction of pro-inflammatory cytokines and type I interferons (IFNs), respectively. To examine possible host-species differences in NF-ĸB function, we compared the antiviral role of NF-κB between pig and human primary and immortalised respiratory epithelial cells infected with IAV. Activation of NF-κB in pig cells significantly inhibited IAV replication and induced strong type I IFN associated gene response. In human cells, however, activation of NF-κB had limited effects on IFN associated response and IAV replication. Microarray RNA profiling comparison indicated that basal transcriptional activity of NF-κB associated genes in primary normal human bronchial (NHBE) cells was more active than corresponding genes in primary pig tracheal epithelial cells (PTECs). In particular, TNFRSF1A, a key upstream gene of NF-κB signalling, was found to be highly expressed in NHBE cells. Knockdown of TNFRSF1A in NHBE cells blocked IAV replication, but in PTECs had no effect on virus output. Overexpression of TNFRSF1A in PTECs increased IAV progeny production, but in NHBE cells had limited effect on virus output.